Improved Serotonergic Tone Contributes to the Mechanism of Action of St John’s Wort in Nicotine Withdrawn Mice - Shabana Saeed; Samina Bano (Journal of Pharmacy and Nutrition Sciences, 2014)
Present study aims to investigate the acute effects of St John’s Wort (SJW) on nicotine withdrawal syndrome and serotonergic hypo activity in mice. Adult male Albino mice weighing 20-25g were housed 6 per cage under light and dark conditions at 22±3oC and maintained on lab chow and water ad libitum under standard housing conditions. Nicotine was administered at the concentrations of 3.08mg (1mg of free base) in 100 ml of drinking water for 4 weeks. Nicotine withdrawal was achieved by substituting nicotine containing water with drinking water. Nicotine withdrawn (NW) mice were evaluated for locomotor activity and abstinence signs at 72 h. Whole brain tryptophan (TRP). 5-hydroxytryptamine (5-HT) and 5-hydroxyindoleacetic acid (5-HIAA) were measured using high performance liquid chromatography connected to fluorescence detector. St John’s Wort (SJW) (500mg/kg) was given intraperitonially 3 h prior to completion of 72 h of nicotine withdrawal period. Behavioral analysis in SJW administered NW mice showed attenuation in nicotine abstinence signs (shaking, scratching, chewing and facial tremors) and locomotor activity when compared with respective controls. NW mice showed decrease in plasma TRP, brain TRP and 5-HT concentrations while increase in 5-HT turnover and corticosterone concentrations as compared to respective controls. SJW administrated NW mice showed decrease in corticosterone levels and 5-HT turnover while plasma TRP, brain TRP and 5-HT synthesis were increased when compared with similarly treated saline injected group. Our findings warrant SJW’s therapeutic efficacy to alleviate nicotine withdrawal associated depression by virtue of its ability to improve serotonergic activity by increasing brain TRP, 5-HT concentrations and decreased turnover.